When to claim a pension: the effect of uncertainty in ages at death - Sha Jiang; Wenyun Zuo; Zhen Guo; Shripad Tuljapurkar (Genus)
Abstract When should you claim a pension (such as social security) in the US? Much current advice focuses on the increase in the annual pension benefit as individuals delay claiming a pension, an increase due to the actuarial fairness of the system. However, individuals face two risks: whether they live to the planned claiming age, and how long they live after they claim. By isolating and measuring these two separate demographic risks, we quantify and describe the effect of demographic uncertainty in ages at death on claiming decisions, without the complexities of additional factors. We show that for both individuals and couples, the coefficient of variation of the (combined) lifetime benefit, calculated as the ratio of the standard deviation to the average, increases as individuals/couples delay claiming, indicating a rising risk relative to the benefit. Using a simple utility analysis that only considers lifetime pension benefits, we find a conditional optimal portfolio under different risk aversion levels, suggesting that individuals and couples should consider both average benefit and risk when deciding on a claiming age, as with other investment decisions. This focused approach highlights the important role of lifespan uncertainty in Social Security claiming decisions. We illustrate the flexibility and generality of our approach by applying it to income-based subgroups and deriving analytical solutions under the Gompertz mortality model, though the framework readily extends to other subgroup definitions and mortality assumptions. Our approach highlights one essential component in making a decision, and can be used in conjunction with factors such as wealth and consumption to make a more comprehensive analysis.